RESILIENSI DIGITAL GURU SEKOLAH DASAR TERHADAP PLATFORM MERDEKA MENGAJAR DALAM IMPLEMENTASI KURIKULUM MERDEKA - Rachman, Aditya; Amaliah, Siti; Imamudin, Imamudin; Atfaliyah, Khodiqotul; Novita, Elin; Purwatisari, Ani; Ningsih, Puji Rahayu; Pradanti, Ainia (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Elementary school teachers certainly have various abilities regarding technology learning, in real life young teachers are relatively more skilled at Informational Technology (IT) based learning such as the Merdeka Mengajar Platform (PMM). This research aims to find out how digital resilience teachers are in implementing the Merdeka Curriculum and assess the effectiveness of using the Merdeka Mengajar Platform on the effectiveness of the learning process in elementary schools. This research method is descriptive qualitative with the data source used in this research being a primary data source consisting of the results of interviews with 10 elementary school teachers in Serang City. The data collection technique in this research uses interviews and data analysis uses thematic analysis techniques. Most teachers have been effective in implementing PMM. Meanwhile, only a small number of teachers use PMM optimally. In taking part in the webinar training, almost all teachers took part. However, there are still few senior teachers who can understand the PMM application. This is supported by the results of interviews conducted with ten elementary school teachers in the city of Serang